Electoral Campaigning in the German Länder: Beyond the Discourse of Professionalization - Lewandowsky, Marcel (Momentum Quarterly, 2013)
According to the mainstream in political science, electoral campaigning becomes more and more professionalized. During phases of campaigning, parties are expected to adopt certain forms of centralized organization, act according to the results of polls and make use of marketing instruments. However, even if this is true for electoral campaigning on the national level, things might look different on the sub-national level if one takes self-rule into account. Built on a broader study which is based on interviews, this enquiry aims to analyze organizational practices and forms in electoral campaigning in three German Länder.
Keywords: electoral campaigning; political parties; strategy